Epileptic encephalopathy-causing mutations in DNM1 impair synaptic vesicle endocytosis - Dhindsa,RS; Bradrick,SS; Yao,X; Heinzen,EL; Petrovski,S; Krueger,BJ; Johnson,MR; Frankel,WN; Petrou,S; Boumil,RM; Goldstein,DB (Neurology: Genetics, 2015)
OBJECTIVE: To elucidate the functional consequences of epileptic encephalopathy-causing de novo mutations in DNM1 (A177P, K206N, G359A), which encodes a large mechanochemical GTPase essential for neuronal synaptic vesicle endocytosis. METHODS: HeLa and COS-7 cells transfected with wild-type and mutant DNM1 constructs were used for transferrin assays, high-content imaging, colocalization studies, Western blotting, and electron microscopy (EM). EM was also conducted on the brain sections of mice harboring a middle-domain Dnm1 mutation (Dnm1 (Ftfl)). RESULTS: We demonstrate that the expression of each mutant protein decreased endocytosis activity in a dominant-negative manner. One of the G-domain mutations, K206N, decreased protein levels. The G359A mutation, which occurs in the middle domain, disrupted higher-order DNM1 oligomerization. EM of mutant DNM1-transfected HeLa cells and of the Dnm1 (Ftfl) mouse brain revealed vesicle defects, indicating that the mutations likely interfere with DNM1's vesicle scission activity. CONCLUSION: Together, these data suggest that the dysfunction of vesicle scission during synaptic vesicle endocytosis can lead to serious early-onset epilepsies.